Swami Vivekananda In Kerala - R. , R.Subramony (International Journal of Psychosocial Rehabilitation, 2020)
Synopsis: Swami Vivekananda's epoch-making visit to Kerala in the early 1890s has to be studied in detail. A chance meeting with Dr.Palpu in Bangalore made them change their itinerary and plan a visit to Kerala. This visit culminated in the historic three-day meditation on ‘the last bit of Indian rock’ in the sea at Kanyakumari.